LEGAL TRANSLATION AND PROBLEMS IN TRANSLATING DOCUMENTS IN THE UNITED NATIONS. (Arab Journal for Humanities & Social Sciences, 2024)
Legal translation is translating legal documents and materials from one language to another. It is a specialized field that requires a high level of accuracy and attention to detail, as even small mistakes can have significant consequences in the legal system. Legal translation is often used in international organizations such as the United Nations, where documents must be translated into multiple languages to be understood by all parties involved. One of the main challenges in legal translation is the need for a precise and accurate translation of technical terms and legal terminology. These terms often have specific meanings in the legal context and can be difficult to translate accurately. For example, the term "contract" may have different meanings in different legal systems, and the translator must be familiar with the legal system of both the source and target languages to convey the meaning of the term accurately. Another challenge in legal translation is the need to translate legal concepts and principles accurately. These concepts are often deeply rooted in the culture and legal system of the source language and may not have an equivalent in the target language. This can make it difficult to convey the full meaning and context of the original text. In addition to the technical challenges of legal translation, practical challenges can also arise. For example, the translator may need to work with multiple languages and legal systems simultaneously, which can be time-consuming and complex. The translator may also need to work with a large volume of documents, which can be overwhelming and require specialized tools and software to manage the translation process. The United Nations is a global organization that operates in multiple languages and legal systems, making legal translation an essential part of its operations. The UN uses legal translators to translate many documents, including treaties, agreements, and other legal materials. However, translating these documents can be a complex and challenging process due to the technical and practical challenges described above.